Surveillance, Epidemiology and Impact of EV-A71 Vaccination on Hand, Foot, and Mouth Disease in Nanchang, China, 2010–2019 - He, Fenglan; Rui, Jia; Deng, Zhiqiang; Zhang, Yanxia; Qian, Ke; Zhu, Chunhui; Yu, Shanshan; Tu, Junling; Xia, Wen; Zhu, Qingxiong; Chen, Shengen; Chen, Tianmu; et al. (Frontiers in Microbiology, 2022)
After the first national-scale outbreak of Hand, foot and mouth disease (HFMD) in China, a national surveillance network was established. Here we described the epidemiology and pathogenic profile of HFMD and the impact of EV-A71 vaccination on pathogen spectrum of enteroviruses in the southeastern Chinese city of Nanchang during 2010-2019. A total of 7951 HFMD cases from sentinel hospitals were included, of which 4800 EV-positive cases (60.4%) were identified by real-time RT-PCR. During 2010-2012, enterovirus 71 (EV-A71) was the main causative agent of HFMD, causing 63.1% of cases, followed by 19.3% cases associated with coxsackievirus A16 (CV-A16). Since 2013, the proportion of other enteroviruses has increased dramatically, with the sub genotype D3 strain of Coxsackievirus A6 (CV-A6) replacing the dominance of EV-A71. These genetically diverse native strains of CV-A6 have co-transmitted and co-evolved in Nanchang. Unlike EV-A71 and CV-A16, most CV-A6 infections were concentrated in autumn and winter. The incidence of EV-A71 infection negatively correlated with EV-A71 vaccination (r=-0.990, p=0.01). And severe cases sharply declined as the promotion of EV-A71 vaccines. And after 2-year implementation of EV-A71 vaccination, EV-A71 is no longer detected from the reported HFMD cases in Nanchang. In conclusion, EV-A71 vaccination changed the pattern of HFMD epidemic, and CV-A6 replaced the dominance of EV-A71 over time.